Reflecting on Efficacy of Meanings Into Words Intermediate - Sah, Kedar Prasad (Academic Voices: A Multidisciplinary Journal, 2011)
The present paper is an attempt to share some reflections on the effectiveness of the textbook ‘Meanings into Words Intermediate’ prescribed by Higher Secondary Education Board for the students of grade XI. This largely draws on my experience of teaching the course for more than a decade. Keywords Communicative approach, notional-functional syllabus, controlled practice, free practice, Presentation-Practice-Production (PPP) DOI: http://dx.doi.org/10.3126/av.v1i0.5304 Academic Voices 2011; 1: 23-25